Les cérémonies d’accueil dans la citoyenneté française et les « citizenship ceremonies » en Grande-Bretagne : quelques éléments de comparaison - Catherine Puzzo (Cahiers du MIMMOC)
Over the past few years citizenship ceremonies for those acquiring British or French citizenship have been held in both countries. For the candidates these official celebrations mark the end of often lengthy administrative procedures to get naturalised and testify to their commitment to integrate into their new country. Both countries are intent to give a more political and ideological significance to the process of naturalisation. Conditions imposed on candidates, like the language tests and the UK life test are supposed to be for the host countries an unquestionable indication that each new citizen has a minimum knowledge about his/her new country, that he/she understands and respects its democratic values. Beyond the formal and theoretical aspects of these ceremonies, the differences observed reflect the diversity of the two models of integration.